2021
DOI: 10.1002/mnfr.202100893
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Function Relationships of Human Milk Oligosaccharides on the Intestinal Epithelial Transcriptome in Caco‐2 Cells and a Murine Model of Necrotizing Enterocolitis

Abstract: Scope Necrotizing enterocolitis (NEC) is a devastating gastrointestinal emergency affecting preterm infants. Breastmilk protects against NEC, partly due to human milk oligosaccharides (HMOs). HMO compositions are highly diverse, and it is unclear if anti‐NEC properties are specific to carbohydrate motifs. Here, this study compares intestinal epithelial transcriptomes of five synthetic HMOs (sHMOs) and examines structure–function relationships of HMOs on intestinal signaling. Methods and Results This study inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…HMOs are reported to exert a number of protective effects in the intestinal tract, including the stimulation of the growth of commensal bacteria [ 24 , 25 ], inhibition of the growth of enteric pathogens and elaborated toxins [ 13 , 26 ], promotion of goblet cell-derived mucin production and secretion [ 27 ], modulation of both innate and adaptive immunity [ 28 ] and maintenance of the integrity of the epithelial cell barrier [ 17 , 19 ]. Traditionally, the structure and specificity of responses of HMOs are associated with effects on microbial functions related to their role either as prebiotics or anti-adhesive molecules [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…HMOs are reported to exert a number of protective effects in the intestinal tract, including the stimulation of the growth of commensal bacteria [ 24 , 25 ], inhibition of the growth of enteric pathogens and elaborated toxins [ 13 , 26 ], promotion of goblet cell-derived mucin production and secretion [ 27 ], modulation of both innate and adaptive immunity [ 28 ] and maintenance of the integrity of the epithelial cell barrier [ 17 , 19 ]. Traditionally, the structure and specificity of responses of HMOs are associated with effects on microbial functions related to their role either as prebiotics or anti-adhesive molecules [ 3 ].…”
Section: Discussionmentioning
confidence: 99%
“…These observations confirm previous studies, where it has been postulated that epithelial barrier protection is a core function, which is common in various HMOs. For instance, Natividad et al showed, using a mixture of fucosylated, sialylated and acetylated synthetic HMOs at physiologic concentrations, an increase in TER in polarized epithelial (Caco-2 and HT-29) cells, whereas exposure to any one oligosaccharide alone did not result in an increase in TER [ 17 ]. HMOs may also act to promote gut homeostasis via the induction of mucin production [ 19 ] and enhanced glycocalyx expression [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that individual HMOs had different degrees of protection against NEC. However, their mechanisms were different, indicating that the protective effect of HMOs on NCE was related to their structures . In addition to intestinal inflammation-related diseases, studies have found that HMO can delay and inhibit the development of type I diabetes in non-obese diabetic mice and can also improve psoriasis in mice induced by imiquimod, a chronic immune-mediated inflammatory skin disease …”
Section: Hmos As a New Potential Food Bioactive Componentmentioning
confidence: 99%
“…Wu et al explored the intestinal epithelial transcriptome of five HMOs (2′-FL, 3-FL, LNnT, LNT, and 6′-SL). They found that different HMOs can protect against intestinal barrier damage and inflammation, but each HMO regulates a unique signal pathway . In addition, HMOs have also been proven to enhance gut barrier function by stimulating the development of glycocalyx on intestinal epithelial cells. , Therefore, HMOs may prevent the development of diabetes by maintaining the integrity of the gut barrier.…”
Section: Hmos As a New Potential Food Bioactive Componentmentioning
confidence: 99%